(untitled) (Journal of Nobel Medical College, 2015)
Objectives To determine the health status and the factors affecting health seeking behavior of the senior citizens aged 60years and above. Materials and methods A descriptive cross-sectional study based on household survey was adapted. The sample consisted of 400 senior citizens resident of Dharan. Simple random sampling technique was employed to select the study subject. Individuals were interviewed through self- developed semi-structured pre-tested questionnaires. Descriptive and inferential statistics (chi-squire test) were used. Results Among 400 respondents, the most frequently reported illness were hypertension(29.3%), diabetes mellitus (8.3%), arthritis/joint pain (24.8%), eye problems (19.0%), hearing problems (3.3%), oral health problems (17.5%), digestive system problems (17.8%), respiratory problems (11.0%), heart disease (3.8%), renal problem (5.3%), skin diseases (7.5%), tuberculosis (3.0%), liver disease (3.0%), mental illness (5.75%),fracture (1.0%), Gynecological problems (7.3%) and male genital (6.3%) problems were also noted. Faith healers were the first treatment choice (97.2%) irrespective of age, gender or ethnicity. After that they visited BPKIHS (36.3%), private practitioner (26.3%), self treatment (11.3%) and self drug-use (6.8%). Half of the respondents utilized formal health institutions only in major chronic conditions. Poverty emerged as a major determinant of health seeking behavior and treatment was considered waste of money (indirect effect 64%) and lack of money (35 .5%) followed by poor attitude of health worker (41%). Conclusion The use of faith healer as first treatment provider, self-treatment, drug over counter shop were indicative factors of the inefficient utilization of health facilities in meeting the health needs of the senior citizens, were ranked the major determinants of factors affecting health seeking behavior of the senior citizens. Journal of Nobel College of Medicine Vol.4(1) 2015: 57-63